Modernization of Professional Training of Electromechanics Bachelors: ICT-based Competence Approach - Модло, Євгеній; Семеріков, Сергій; Шмельцер, Катерина (Pedagogy of Higher and Secondary Education, 2018)
Modlo Yе.O., Semerikov S.O. and Shmelttser K.O. Modernization of Professional Training of Electromechanics Bachelors: ICT-based Competence Approach. Analysis of the standards for the preparation of electromechanics in Ukraine showed that the electromechanic engineer is able to solve complex specialized problems and practical problems in a certain area of professional activity or in the process of study. These problems are characterized by complexity and uncertainty of conditions. The main competencies include social-personal, general-scientific, instrumental, general-professional and specialized-professional. A review of scientific publications devoted to the training of electromechanics has shown that four branches of engineering are involved in the training of electromechanical engineers: mechanical and electrical engineering (with a common core of electromechanics), electronic engineering and automation. The common use of the theory, methods and means of these industries leads to the emergence of a combined field of engineering — mechatronics. Summarizing the experience of electrical engineers professional training in Ukraine and abroad makes it possible to determine the main directions of their professional training modernization.